Remote investing in Latin America, 1869-1929 - Gareth Campbell; Áine Gallagher; Richard S. Grossman (Queen's University Centre for Economic History (QUCEH), 2025)
Substantial amounts of British capital flowed to Latin America during the first era of globalisation. Companies financed by this capital were typically headquartered in the UK, but operated thousands of miles away. This paper asks how this geographic separation between governance and business activities affected the valuation of these firms. We find that the location of the headquarters played a more important role than the location of operations. Stock prices tended to fluctuate in line with other equities based in the UK, suggesting that they were still regarded as being, at least partially, British companies.
Keywords: F21; F54; F65; G11; G12; G15; G51; N16; N26; 330; Latin America; equity markets; portfolio investing; emerging markets